A153: Long‐term Outcomes of Childhood‐Onset Systemic Lupus Erythematosus in Adulthood. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Levy, Deborah M.; Gunraj, Nadia; Berard, Roberta A.; Dent, Peter B.; Pope, Janet E.; Thorne, J. Carter; Roth, Johannes; Fidler, Wesley; Berall, Murray; Guttmann, Astrid; Silverman, Earl D.
Abstract : Background/Purpose: Little is known about the long‐term morbidity and mortality of childhood‐onset SLE (cSLE) after transition to adult care; however, linking clinical data to administrative databases enables study of previously unknown outcomes. Our objectives were to describe long‐term outcomes in young adults with cSLE, including: i) cardiovascular outcomes; ii) renal outcomes; iii) joint replacement surgery due to avascular necrosis; iv) malignancies; and v) pregnancies and births. Methods: A retrospective chart review of all cSLE patients (<18 years at diagnosis) diagnosed between Jan 1, 1984 and Dec 31, 2011 and followed for ≥1 year was conducted after contacting all pediatric and adult rheumatologists and nephrologists practicing in Ontario. Clinical data and Ontario Health Insurance Plan (OHIP) numbers were securely transferred to the Institute for Clinical Evaluative Sciences (ICES). OHIP numbers were transformed into an encrypted ICES key number (IKN) used to link the cohort to multiple administrative datasets to determine the outcomes of interest. Outcomes were determined using validated definitions. Means ± standard deviations are given unless noted. Results: 622 cSLE patients are included in this inception cohort. The cohort was predominantly female (81%) with mean follow‐up of 10.7 ± 7.3 years, representing 6629 person‐years of disease. Age at diagnosis was 12.8 ± 3.2 years. There were 34 (6%) hospitalizations for cerebrovascular events, at mean age 18.1 ± 7.7 years, and disease duration 6.7 ± 7.0 years. Fewer than 6 hospitalizations for myocardial infarctions occurred at a median disease duration of 10.7 years. 273 (44%) patients had biopsy‐proven lupus nephritis, with end stage renal disease occurring in 20 (7.3%) of these patients at mean age 31.4 ± 8.0 years, and disease duration 17.5 ± 8.7 years. Eight patients underwent renal transplant. Twenty‐two (3.5%) patients have had 32 hip replacement surgeries, at mean age 24.2 ± 6.6 years and disease duration 10.1 ± 6.7 years. Fewer than 6 patients have had knee and/or ankle replacement surgery. Fourteen malignancies occurred in 13 (2%) patients, at mean age 28.2 ± 9.2 years and disease duration 16.5 ± 7.2 years. Nine were female reproductive and/or hematologic malignancies. Obstetrical outcomes were examined in females ages 15–45 years. Of 222 pregnancies, there were 82 (37%) live births, occurring at mean age 26.4 ± 4.9 years and disease duration 12.1 ± 5.5 years. Fewer than 6 pregnancies resulted in twins. There were 90 (41%) therapeutic abortions, 39 (18%) miscarriages, and 8 (4%) still births. Conclusion: Myocardial infarction and end‐stage renal failure rates in this cohort with universal healthcare appear to be lower than reported in other populations. Cerebrovascular disease, hip replacement surgery and malignancies were significant morbidities in this cohort of young adults. Many women were able to conceive and deliver live infants; however, the miscarriage and stillbirth rates were greater than expected for young women.